After the prints of our caring origins - Mercedes Núñez del Castillo; José Siles González (Universidad de Alicante, 2012)
The aim of this work is to demonstrate that iconography becomes a source for nursing history. A descriptive, retrospective, comparative, ethnographic historical study was carried out. The iconographic material used corresponds to cave paintings from the Valencian County, declared world's heritage. In order to potentiate the hermeneutical process from a nursing perspective, the Henderson's needs system categorisation has been used. The main conclusion of this study is the demonstration of the pertinence of iconography when it comes to developing historical knowledge of nursing.